High-insulation low-loss soft magnetic composite material and preparation method and application thereof
By generating a Li2O-Al2O3-ZnO-B2O3-SiO2 glass cladding layer in situ on the surface of magnetic particles, the problems of easy cracking and low bonding strength of SiO2 insulating cladding layers in the prior art are solved, and a high-insulation, low-loss soft magnetic composite material is prepared, which is suitable for new energy vehicles and aerospace inductors.
Patent Information
- Application Number
- CN202611238494.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-15
- Publication Date
- 2026-11-03
AI Technical Summary
Existing technologies struggle to form a dense, crack-free SiO2 insulating coating with high interfacial bonding strength and high voltage resistance on the surface of magnetic particles at low temperatures, resulting in insufficient insulation and voltage resistance performance and high losses in soft magnetic composite materials.
Li2O-Al2O3-ZnO-B2O3-SiO2 glass was used as a low-melting-point glass insulating layer. It was in-situ coated onto the surface of magnetic particles and a dense glass coating layer was formed by gradient heat treatment. The interfacial bonding strength was improved by chemical bonding, and the viscous flow of the low-melting-point glass was used to eliminate microcracks.
A soft magnetic composite material with extremely high surface resistance, low loss, and high permeability was prepared at a relatively low temperature, which is suitable for new energy vehicle drive motors, 5G base station power supplies, or aerospace inductors.
Smart Images

Figure CN123033853A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of soft magnetic materials technology, specifically relating to a high-insulation, low-loss soft magnetic composite material, its preparation method, and its application. Background Technology
[0002] Soft magnetic composite materials (SMC), also known as magnetic powder cores, are key materials for manufacturing high-frequency inductors, transformers, and motor cores. It is well known that to reduce high-frequency eddy current losses in soft magnetic composite materials, a high-resistivity insulating layer is typically formed between the magnetic particles. SiO2, with its high resistivity and good thermal stability, is an insulating coating material with broad application prospects. Currently, SiO2 insulating coatings are mainly prepared using the sol-gel method with tetraethyl orthosilicate (TEOS) as a precursor, but this method has the following drawbacks: 1) Microcracks easily form in the SiO2 insulating coating during drying and heat treatment, leading to insufficient insulation withstand voltage of the soft magnetic composite material; 2) Excessively high densification temperatures (>800℃) easily cause oxidation of the magnetic powder and degradation of magnetic properties; 3) The bonding strength between the SiO2 insulating coating and the magnetic powder interface is low, and the SiO2 insulating coating is easily damaged during high-pressure molding, further reducing the withstand voltage strength of the soft magnetic composite material.
[0003] Studies have shown that introducing a glass phase is an effective strategy to improve the density and pressure resistance of the insulating coating layer on the surface of magnetic particles. However, existing glass coating methods (such as mechanical mixing of glass powder and melt spraying) are difficult to achieve uniform nanoscale coating, and the preparation process is complex and costly, making it difficult to fully meet the needs of practical applications.
[0004] Therefore, it is of great significance to develop a method that can form a dense, crack-free, high interfacial bonding strength, high voltage resistance, and low loss insulating coating layer in situ on the surface of magnetic particles at a lower temperature, and to prepare soft magnetic composite materials with extremely high surface resistance, extremely low high-frequency loss, high magnetic permeability, and good frequency stability.
[0005] The above statements are merely background information related to the present invention and do not necessarily constitute prior art. Summary of the Invention
[0006] The purpose of this invention is to provide a high-insulation, low-loss soft magnetic composite material, its preparation method, and its application.
[0007] The technical solution adopted in this invention is:
[0008] A high-insulation, low-loss soft magnetic composite material is composed of soft magnetic powder with a low-melting-point glass insulating layer in situ coated on its surface. The low-melting-point glass insulating layer is composed of Li2O-Al2O3-ZnO-B2O3-SiO2 glass.
[0009] Preferably, the thickness of the low-melting-point glass insulating layer is 20nm to 100nm.
[0010] Preferably, the glass transition temperature (T2) of the Li2O-Al2O3-ZnO-B2O3-SiO2 glass is [missing information]. g The temperature range is 450℃~520℃, and the softening point is ≤580℃.
[0011] Preferably, the soft magnetic powder is at least one of iron-silicon-aluminum (FeSiAl) powder, iron-nickel (FeNi) powder, iron-silicon (FeSi) powder, pure iron powder, and carbonyl iron powder.
[0012] Preferably, the D of the soft magnetic powder 50 The particle size ranges from 5 μm to 100 μm.
[0013] A method for preparing a high-insulation, low-loss soft magnetic composite material as described above includes the following steps:
[0014] 1) Preparation of pretreated soft magnetic powder and composite sol precursor solution:
[0015] Preparation of pretreated soft magnetic powder: The soft magnetic powder is acid-washed, water-washed and dried to obtain pretreated soft magnetic powder;
[0016] Preparation of the composite sol precursor: Lithium nitrate, aluminum nitrate, zinc acetate, and boric acid were dissolved in water to prepare an aqueous solution, and tetraethyl orthosilicate was dissolved in ethanol to prepare an ethanol solution of tetraethyl orthosilicate. The aqueous solution was then slowly added to the ethanol solution of tetraethyl orthosilicate (TEOS) under stirring. After the addition was complete, the mixture was stirred to react, yielding the composite sol precursor. (In this composite sol precursor, the silicic acid produced by the partial hydrolysis of TEOS reacts with Li...) + Al 3+ Zn 2+ (B(OH)3 forms a homogeneous sol system).
[0017] 2) Add the pretreated soft magnetic powder to the composite sol precursor solution, then adjust the pH of the system to 8-10 before proceeding with the reaction (during this process, TEOS continuously hydrolyzes and condenses, while Li...). + Al 3+ Zn 2+ Boric acid is uniformly distributed in the growing SiO2 gel network through electrostatic adsorption, coordination or condensation with silanol groups to form a composite precursor coating layer containing Li-Al-Zn-B-Si. The thickness of the coating layer can be controlled by reaction time and precursor concentration. Then, the product is separated, purified and dried to obtain coated soft magnetic powder.
[0018] 3) The coated soft magnetic powder is subjected to gradient heat treatment in an inert or reducing atmosphere:
[0019] The first stage (pre-curing and removal of organic matter): control the heating rate to 2℃ / min~5℃ / min from room temperature to 150℃~250℃, and hold at this temperature for 0.5h~1h (during this process, the solvent, acetate, nitrate and other substances in the gel network decompose and volatilize, and preliminary condensation occurs at the same time).
[0020] The second stage (glass transition and densification): The heating rate is controlled at 1℃ / min~3℃ / min, continuing to heat to 480℃~580℃, and held for 0.5h~2h. (During this process, the Li2O-Al2O3-ZnO-B2O3-SiO2 multi-component system undergoes a glass transition to form low-melting-point glass.) g At approximately 450℃~520℃, the glassy liquid phase or viscous flow can fill the original micropores and cracks of the SiO2 gel, achieving self-healing and complete densification. At the same time, it forms chemical bonds such as Fe-O-Si, Fe-O-Al, and Fe-O-Zn with iron oxides or iron atoms on the surface of the magnetic powder, which can significantly improve the interfacial bonding strength.
[0021] The third stage (rapid cooling): control the cooling rate to ≥10℃ / min to cool to room temperature (during this process, the glass network structure freezes, which can prevent crystallization) to obtain heat-treated soft magnetic powder;
[0022] 4) Mix the heat-treated soft magnetic powder and lubricant, then mold it, and then anneal it in a protective atmosphere to obtain a high-insulation, low-loss soft magnetic composite material.
[0023] Preferably, the acid solution used in step 1) for pickling is at least one of citric acid solution and dilute hydrochloric acid solution.
[0024] Preferably, the citric acid solution has a mass fraction of 0.2% to 0.8%.
[0025] Preferably, the pickling method in step 1) is ultrasonic cleaning, and the pickling time is 10 min to 20 min.
[0026] Preferably, the drying method in step 1) is vacuum drying.
[0027] Preferably, the molar ratio of tetraethyl orthosilicate, lithium nitrate, aluminum nitrate, zinc acetate, and boric acid in step 1) is 1:0.05~0.40:0.05~0.25:0.05~0.20:0.1~1.0.
[0028] Preferably, the molar ratio of tetraethyl orthosilicate to water in step 1) is 1:4 to 25.
[0029] Preferably, the molar ratio of tetraethyl orthosilicate and ethanol in step 1) is 1:6 to 20.
[0030] Preferably, the stirring reaction time in step 1) is 30 min to 60 min.
[0031] Preferably, the ratio of the pretreated soft magnetic powder and the composite sol precursor solution in step 2) is 1g:6mL to 15mL.
[0032] Preferably, the pH adjuster used in step 2) is ammonia water with a concentration of 0.1 mol / L to 0.5 mol / L.
[0033] Preferably, the reaction in step 2) is carried out at a temperature of 40℃ to 60℃ for a reaction time of 2h to 5h.
[0034] Preferably, the product separation and purification in step 2) includes the following process: first, the powder is separated by magnetic decantation or filtration, and then washed 2 to 3 times with anhydrous ethanol.
[0035] Preferably, the drying method in step 2) is vacuum drying.
[0036] Preferably, the mass ratio of the soft magnetic powder and the lubricant in step 4) is 1:0.003 to 0.015.
[0037] Preferably, the lubricant in step 4) is at least one of zinc stearate and lithium stearate.
[0038] Preferably, the compression molding in step 4) is carried out under a pressure of 1000MPa to 1800MPa.
[0039] Preferably, the annealing in step 4) is carried out at a temperature of 650℃~700℃ for a time of 0.5h~1h.
[0040] Application of a high-insulation, low-loss soft magnetic composite material as described above in new energy vehicle drive motors, 5G base station power supplies, or aerospace inductors.
[0041] The innovative aspects of this invention are as follows:
[0042] 1) In-situ generation of low-melting-point glass coating: Li, Al, Zn and B multi-element glass network modifiers are introduced into the TEOS sol-gel system. Through molecular-level mixing and heat treatment, a dense glass coating is formed in-situ at 480℃~580℃, avoiding the complex process of traditional glass coating.
[0043] 2) Mechanism for achieving high voltage resistance: The glass coating is crack-free, pore-free, and has a uniform thickness (20nm~100nm). Its breakdown field strength can reach 300V / μm~500V / μm. At the same time, the glass phase and magnetic powder form a chemical bond interface, which will not break during high pressure molding (≥1500MPa). This makes the surface insulation resistance of the soft magnetic composite material ≥1GΩ, which is more than two orders of magnitude higher than that of traditional SiO2 coated soft magnetic composite materials (MΩ level).
[0044] 3) Ultra-low loss design: The resistivity of the glass coating is as high as 10. 9 Ω·cm~10 11 Ω·cm can significantly suppress eddy current losses. Simultaneously, the viscous flow of low-melting-point glass during heat treatment can eliminate microcracks and avoid localized eddy current concentration. Furthermore, the Li in the glass composition... + and Zn 2+ It can reduce the heat treatment temperature (≤580℃), effectively suppress the oxidation of magnetic powder, and maintain low hysteresis loss;
[0045] 4) Enhanced interfacial chemical bonding: By introducing Al and Zn elements, Fe-O-Al and Fe-O-Zn bonds are generated by reacting with iron oxides on the surface of magnetic powder during heat treatment, which increases the interfacial bonding strength by 3 to 5 times and ensures that the coating layer is intact after pressing.
[0046] 5) Adjustable composition: By adjusting the ratio of Li, Al, Zn, and B, the coefficient of thermal expansion of the glass (6×10⁻⁶) can be precisely controlled. -6 / K~12×10 -6 / K), so that it can be combined with different magnetic powders (FeSiAl has a thermal expansion coefficient of about 11×10). -6 / K, the coefficient of thermal expansion of FeNi is approximately 9×10⁻⁶. -6 The matching of / K) further reduces thermal stress and improves the reliability of the insulation coating.
[0047] The beneficial effects of this invention are: this invention can form a dense, crack-free, high interfacial bonding strength, high withstand voltage, and low loss insulating coating layer in situ on the surface of magnetic particles at a relatively low temperature, thereby preparing a soft magnetic composite material with extremely high surface resistance, extremely low high-frequency loss, high magnetic permeability, and good frequency stability, which is suitable for use in new energy vehicle drive motors, 5G base station power supplies, or aerospace inductors.
[0048] Specifically:
[0049] 1) Extremely high withstand voltage performance: The surface insulation resistance of the soft magnetic composite material of the present invention is high (>1GΩ; test conditions: toroidal magnetic core, test voltage 300V), which is much higher than the MΩ level of the traditional TEOS-SiO2 coated soft magnetic composite material;
[0050] 2) Ultra-low high-frequency loss: The soft magnetic composite material of this invention has extremely low high-frequency loss (the total loss P of the FeSiAl-based soft magnetic composite material at 1MHz / 50mT is...). cv ≤1000mW / cm 3 The total loss P of FeNi-based soft magnetic composite materials at 1MHz / 50mT cv ≤700mW / cm 3 );
[0051] 3) High permeability and frequency stability: The soft magnetic composite material of this invention has high permeability (the effective permeability μ of the FeSiAl-based soft magnetic composite material at 1MHz is...). e The effective permeability μ of the FeNi-based soft magnetic composite material at 1 MHz is 60–80. e With a permeability of 60–120 μ, and good frequency stability (effective permeability μ in the 80 MHz range), this product exhibits excellent permeability. e The rate of change is <5%. Attached Figure Description
[0052] Figure 1 This is a TEM image of the heat-treated soft magnetic powder in Example 1.
[0053] Figure 2 The graph shows the surface resistivity test results of the high-insulation, low-loss soft magnetic composite material of Example 1 and the soft magnetic composite materials of Comparative Examples 1 to 3.
[0054] Figure 3 The core loss-frequency relationship curve of the high-insulation, low-loss soft magnetic composite material in Example 1 is shown.
[0055] Figure 4 This is a TEM mapping image of the high-insulation, low-loss soft magnetic composite material of Example 2. Detailed Implementation
[0056] The present invention will be further explained and described below with reference to specific embodiments.
[0057] Example 1:
[0058] A high-insulation, low-loss soft magnetic composite material is prepared by the following method:
[0059] 1) Preparation of pretreated soft magnetic powder and composite sol precursor solution:
[0060] Preparation of pretreated soft magnetic powder: 100g of FeSiAl powder (D 50=11μm, with the composition of Fe-9.5Si-5.5Al) was added to a 0.5% citric acid solution and ultrasonically cleaned for 15 min. Then it was washed with deionized water until the washing solution was neutral. Finally, it was vacuum dried at 80℃ for 60 min to obtain the pretreated soft magnetic powder.
[0061] Preparation of the composite sol precursor solution: 0.69 g (0.01 mol) of lithium nitrate, 1.88 g (0.005 mol) of aluminum nitrate nonahydrate, 0.55 g (0.0025 mol) of zinc acetate dihydrate and 1.55 g (0.025 mol) of boric acid were dissolved in 20 mL of deionized water to prepare an aqueous phase solution. 10.4 g (0.05 mol) of tetraethyl orthosilicate was dissolved in 50 mL of anhydrous ethanol to prepare an ethanol solution of tetraethyl orthosilicate. The aqueous phase solution was then slowly added dropwise to the stirred ethanol solution of tetraethyl orthosilicate. After the addition was complete, stirring was continued for 40 min to obtain the composite sol precursor solution.
[0062] 2) The pretreated soft magnetic powder was added to the composite sol precursor solution and then ultrasonically dispersed for 20 min at an ultrasonic frequency of 60 kHz and an ultrasonic power of 150 W. The mixture was then stirred for 20 min at a stirring speed of 300 rpm. The temperature was then raised to 50 ℃, and the pH of the system was adjusted to 8.5 with 0.2 mol / L ammonia water. The mixture was then stirred for 4 h. Magnetic separation (magnetic decantation) was performed. The solid was washed three times with anhydrous ethanol and then vacuum dried at 80 ℃ for 60 min to obtain the coated soft magnetic powder.
[0063] 3) Place the coated soft magnetic powder in a heat treatment furnace, then introduce nitrogen gas for gradient heat treatment:
[0064] First stage: Control the heating rate to 3℃ / min to raise the temperature from room temperature to 200℃ and hold for 1 hour;
[0065] Second stage: Control the heating rate to 2℃ / min and continue heating to 520℃, then hold for 1 hour;
[0066] Third stage: Control the cooling rate to 15℃ / min to cool down to room temperature, and obtain heat-treated soft magnetic powder;
[0067] 4) Heat-treated soft magnetic powder and zinc stearate are stirred and mixed evenly. The mass ratio of heat-treated soft magnetic powder to zinc stearate is 1:0.008. Then, it is pressed into a ring magnetic core (outer diameter 20 mm, inner diameter 12 mm, height 6 mm) under a pressure of 1600 MPa. Then, it is annealed at 680℃ for 1 h in a nitrogen atmosphere to obtain a high-insulation and low-loss soft magnetic composite material.
[0068] Performance testing:
[0069] 1) The transmission electron microscope (TEM) image of the heat-treated soft magnetic powder in this embodiment is shown below. Figure 1 (a is the overall view, b and c are enlarged views of the parts) as shown.
[0070] Depend on Figure 1 It can be seen that the soft magnetic powder is in situ coated with a continuous, dense, crack-free glass coating layer, and the thickness of the glass coating layer is about 30 nm.
[0071] 2) TEM mapping tests revealed that the glass coating of the heat-treated soft magnetic powder in this embodiment contained not only Si and O elements, but also Zn, B, Li, Al, and other elements, forming a multi-component glass coating.
[0072] 3) The surface resistance of the high-insulation, low-loss soft magnetic composite material of this embodiment was tested using a Keysight E4991B radio frequency impedance analyzer. The test voltage was 300V, the range was 100nA, and the internal resistance was 1MΩ. The surface resistance test results are as follows: Figure 2 As shown.
[0073] Depend on Figure 2 It can be seen that the surface resistance of the high-insulation, low-loss soft magnetic composite material is as high as 1620MΩ, which is extremely high.
[0074] 4) The magnetic properties of the high-insulation, low-loss soft magnetic composite material of this embodiment were tested using a BH analyzer (IWATSU, SY-8218). The test frequency range was 100kHz to 1MHz. m For a value of 50mT, the core loss-frequency relationship curve obtained is as follows: Figure 3 As shown.
[0075] Depend on Figure 3 It can be seen that: the P of the high-insulation, low-loss soft magnetic composite material at 1MHz / 50mT cv 958mW / cm 3 Ultra-low high-frequency loss.
[0076] 5) The permeability of the high-insulation, low-loss soft magnetic composite material of this embodiment was tested using a BH analyzer (IWATSU, SY-8218). The test frequency range was 100kHz to 1MHz. m The effective permeability μ of the high-insulation, low-loss soft magnetic composite material was measured to be 50 mT. e It has a value of 65, indicating high permeability.
[0077] Example 2:
[0078] A high-insulation, low-loss soft magnetic composite material, except that in step 1) during preparation, "FeSiAl powder (D 50=11μm, composition is Fe-9.5Si-5.5Al) etc., replace with "FeNi powder (D 50 =5μm, composition is Fe-50Ni)”, except for the following changes: in step 1), “0.69g (0.01mol) lithium nitrate, 1.88g (0.005mol) aluminum nitrate nonahydrate, 0.55g (0.0025mol) zinc acetate dihydrate and 1.55g (0.025mol) boric acid” are changed to “0.015mol lithium nitrate, 0.008mol aluminum nitrate nonahydrate, 0.004mol zinc acetate dihydrate and 0.035mol boric acid”; and in step 4), “second stage: control the heating rate at 2℃ / min to continue heating to 520℃ and hold for 1h” is changed to “second stage: control the heating rate at 2℃ / min to continue heating to 550℃ and hold for 1h”. Otherwise, it is exactly the same as Example 1.
[0079] Performance testing:
[0080] 1) TEM testing revealed that the surface of the heat-treated soft magnetic powder in this embodiment is in situ coated with a continuous, dense, crack-free glass coating layer with a thickness of approximately 40 nm.
[0081] 2) The TEM mapping image of the heat-treated soft magnetic powder in this embodiment is as follows: Figure 4 As shown.
[0082] Depend on Figure 4 It can be seen that the glass coating of heat-treated soft magnetic powder contains not only Si and O elements, but also Zn, B, Li, Al and other elements, forming a multi-component glass coating.
[0083] 3) The surface resistance of the high insulation and low loss soft magnetic composite material in this embodiment was found to be as high as 1120MΩ by surface resistance testing, which is extremely high.
[0084] 4) The P of the high-insulation, low-loss soft magnetic composite material of this embodiment at 1MHz / 50mT was obtained by magnetic property testing. cv 660mW / cm 3 Ultra-low high-frequency loss.
[0085] 5) The effective magnetic permeability μ of the high-insulation, low-loss soft magnetic composite material of this embodiment was obtained by magnetic permeability testing. e It has a value of 100, indicating high permeability.
[0086] Example 3:
[0087] A high-insulation, low-loss soft magnetic composite material, except that in step 1) during preparation, "FeSiAl powder (D 50=11μm, composition is Fe-9.5Si-5.5Al) etc., replace with "carbonyl iron powder (D 50 =5μm), except for adjusting “0.69g (0.01mol) lithium nitrate, 1.88g (0.005mol) aluminum nitrate nonahydrate, 0.55g (0.0025mol) zinc acetate dihydrate and 1.55g (0.025mol) boric acid” in step 1) to “0.02mol lithium nitrate, 0.01mol aluminum nitrate nonahydrate, 0.005mol zinc acetate dihydrate and 0.04mol boric acid”, and adjusting “second stage: control the heating rate at 2℃ / min to continue heating to 520℃ and hold for 1h” in step 4) to “second stage: control the heating rate at 2℃ / min to continue heating to 500℃ and hold for 1h”, the rest is exactly the same as in Example 1.
[0088] Performance testing:
[0089] 1) TEM testing revealed that the surface of the heat-treated soft magnetic powder in this embodiment is in situ coated with a continuous, dense, crack-free glass coating layer with a thickness of approximately 30 nm.
[0090] 2) TEM mapping tests revealed that the glass coating of the heat-treated soft magnetic powder in this embodiment contained not only Si and O elements, but also Zn, B, Li, Al, and other elements, forming a multi-component glass coating.
[0091] 3) The surface resistance of the high insulation and low loss soft magnetic composite material in this embodiment was found to be as high as 1270MΩ by surface resistance testing, which is extremely high.
[0092] 4) The P of the high-insulation, low-loss soft magnetic composite material of this embodiment at 1MHz / 50mT was obtained by magnetic property testing. cv 2495mW / cm 3 Ultra-low high-frequency loss.
[0093] 5) The effective magnetic permeability μ of the high-insulation, low-loss soft magnetic composite material of this embodiment was obtained by magnetic permeability testing. e It has a value of 45, indicating high permeability.
[0094] Comparative Example 1:
[0095] A soft magnetic composite material is identical to Example 1 except that the preparation process of the composite sol precursor solution in step 1) is adjusted to "dissolve 10.4 g (0.05 mol) of tetraethyl orthosilicate in 50 mL of anhydrous ethanol to prepare an ethanol solution of tetraethyl orthosilicate, and then slowly add 20 mL of deionized water dropwise to the ethanol solution of tetraethyl orthosilicate under stirring. After the addition is complete, continue stirring for 40 min to obtain the sol precursor solution".
[0096] Performance testing:
[0097] 1) TEM testing revealed that the glass coating layer on the surface of the heat-treated soft magnetic powder in this comparative example had obvious microcracks and poor insulation coating effect. The reason is that this method cannot generate a dense glass phase on the surface of the soft magnetic powder.
[0098] 2) The surface resistivity test results of the soft magnetic composite material in this comparative example are as follows: Figure 2 As shown.
[0099] Depend on Figure 2 It can be seen that the surface resistance of the soft magnetic composite material is 45MΩ, which is much lower than that of the high insulation and low loss soft magnetic composite material in Example 1 (1620MΩ). The reason is that the insulation of the coating layer is relatively low.
[0100] 3) The P of the soft magnetic composite material in this comparative example at 1MHz / 50mT was obtained by magnetic property testing. cv 1485mW / cm 3 The insulation and low-loss soft magnetic composite material of Example 1 (958mW / cm) is significantly higher. 3 The reason is that the coating layer is not dense enough.
[0101] 4) The effective magnetic permeability μ of the soft magnetic composite material in this comparative example was obtained by magnetic permeability testing. e It is 65.
[0102] Comparative Example 2:
[0103] A soft magnetic composite material is identical to Example 1, except that the preparation process of the composite sol precursor solution in step 1) is adjusted to "dissolve 1.55g (0.025mol) of boric acid in 20mL of deionized water to prepare an aqueous solution, and dissolve 10.4g (0.05mol) of tetraethyl orthosilicate in 50mL of anhydrous ethanol to prepare an ethanol solution of tetraethyl orthosilicate, and then slowly add the aqueous solution dropwise to the ethanol solution of tetraethyl orthosilicate under stirring. After the addition is complete, stirring is continued for 40min to obtain the composite sol precursor solution".
[0104] Performance testing:
[0105] 1) The comparative example cannot form a glass phase on the surface of soft magnetic powder because the coating layer lacks components that easily form a glass phase.
[0106] 2) The surface resistivity test results of the soft magnetic composite material in this comparative example are as follows: Figure 2 As shown.
[0107] Depend on Figure 2 It can be seen that the surface resistance of the soft magnetic composite material is 56MΩ, which is much lower than that of the high insulation and low loss soft magnetic composite material in Example 1 (1620MΩ). The reason is that the insulation of the coating layer is relatively low.
[0108] 3) The P of the soft magnetic composite material in this comparative example at 1MHz / 50mT was obtained by magnetic property testing. cv 1738mW / cm 3 The insulation and low-loss soft magnetic composite material of Example 1 (958mW / cm) is significantly higher. 3 The reason is that the coating layer is not dense enough.
[0109] 4) The effective magnetic permeability μ of the soft magnetic composite material in this comparative example was obtained by magnetic permeability testing. e It is 60.
[0110] Comparative Example 3:
[0111] A soft magnetic composite material, the preparation method of which is as follows:
[0112] 1) D245 low melting point glass powder (Anmi Micro-Nano New Materials (Guangzhou) Co., Ltd.) and FeSiAl powder (D 50 =11μm, the composition is Fe-9.5Si-5.5Al) is mixed and ball-milled, the mass ratio of D245 low melting point glass powder and FeSiAl powder is 1:0.015, and then placed at 80℃ for vacuum drying for 40min to obtain mixed powder;
[0113] 2) Mix the mixed powder and zinc stearate evenly, with a mass ratio of mixed powder to zinc stearate of 1:0.008. Then press it into a ring-shaped magnetic core (outer diameter of 20 mm, inner diameter of 12 mm, and height of 6 mm) under a pressure of 1600 MPa. Then anneal it in nitrogen at 680°C for 1 h to obtain a soft magnetic composite material.
[0114] Performance testing:
[0115] 1) TEM testing revealed that the glass coating layer on the surface of the heat-treated soft magnetic powder in this comparative example was severely uneven and had poor insulation coating effect. The reason is that it is difficult to form a uniform coating layer through physical coating.
[0116] 2) The surface resistivity test results of the soft magnetic composite material in this comparative example are as follows: Figure 2 As shown.
[0117] Depend on Figure 2 It can be seen that the surface resistance of the soft magnetic composite material is 35kΩ, which is much lower than that of the high insulation and low loss soft magnetic composite material in Example 1 (1620MΩ). The reason is that the insulation performance of the coating layer is relatively low.
[0118] 3) The P of the soft magnetic composite material in this comparative example at 1MHz / 50mT was obtained by magnetic property testing. cv >10000mW / cm 3 The insulation and low-loss soft magnetic composite material of Example 1 (958mW / cm) is significantly higher. 3 The reason is that the coating effect is poor and cannot effectively limit eddy current loss.
[0119] 4) The effective magnetic permeability μ of the soft magnetic composite material in this comparative example was obtained by magnetic permeability testing. e It is 61.
[0120] Comparative Example 4:
[0121] A soft magnetic composite material is identical to that in Example 2, except that the ingredients in step 1) are changed from "0.015 mol lithium nitrate, 0.008 mol aluminum nitrate nonahydrate, 0.004 mol zinc acetate dihydrate and 0.035 mol boric acid" to "0.008 mol aluminum nitrate nonahydrate, 0.004 mol zinc acetate dihydrate and 0.035 mol boric acid".
[0122] Performance testing:
[0123] The P of the soft magnetic composite material in this comparative example at 1MHz / 50mT was obtained by magnetic property testing. cv 2296mW / cm 3 The insulation and low-loss soft magnetic composite material of Example 2 (660mW / cm) is significantly higher. 3 The reason is that a dense glassy coating layer failed to form.
[0124] Comparative Example 5:
[0125] A soft magnetic composite material is identical to that in Example 2, except that the ingredients in step 1) are changed from "0.015 mol lithium nitrate, 0.008 mol aluminum nitrate nonahydrate, 0.004 mol zinc acetate dihydrate and 0.035 mol boric acid" to "0.015 mol lithium nitrate, 0.004 mol zinc acetate dihydrate and 0.035 mol boric acid".
[0126] Performance testing:
[0127] The P of the soft magnetic composite material in this comparative example at 1MHz / 50mT was obtained by magnetic property testing. cv 1534mW / cm 3 The insulation and low-loss soft magnetic composite material of Example 2 (660mW / cm) is significantly higher. 3 The reason is that a dense glassy coating layer failed to form.
[0128] Comparative Example 6:
[0129] A soft magnetic composite material is identical to that in Example 2, except that the ingredients in step 1) are changed from "0.015 mol lithium nitrate, 0.008 mol aluminum nitrate nonahydrate, 0.004 mol zinc acetate dihydrate and 0.035 mol boric acid" to "0.015 mol lithium nitrate, 0.008 mol aluminum nitrate nonahydrate and 0.035 mol boric acid".
[0130] Performance testing:
[0131] The P of the soft magnetic composite material in this comparative example at 1MHz / 50mT was obtained by magnetic property testing. cv 1236mW / cm 3 The insulation and low-loss soft magnetic composite material of Example 2 (660mW / cm) is significantly higher. 3 The reason is that a dense glassy coating layer failed to form.
[0132] Comparative Example 7:
[0133] A soft magnetic composite material is identical to that in Example 2, except that the ingredients in step 1) are changed from "0.015 mol lithium nitrate, 0.008 mol aluminum nitrate nonahydrate, 0.004 mol zinc acetate dihydrate and 0.035 mol boric acid" to "0.015 mol lithium nitrate, 0.008 mol aluminum nitrate nonahydrate and 0.004 mol zinc acetate dihydrate".
[0134] Performance testing:
[0135] The P of the soft magnetic composite material in this comparative example at 1MHz / 50mT was obtained by magnetic property testing. cv 4578mW / cm 3 The insulation and low-loss soft magnetic composite material of Example 2 (660mW / cm) is significantly higher. 3 The reason is that a dense glassy coating layer failed to form.
[0136] Comparative Example 8:
[0137] A soft magnetic composite material is identical to that in Example 2, except that the ingredients in step 1) are changed from "0.015 mol lithium nitrate, 0.008 mol aluminum nitrate nonahydrate, 0.004 mol zinc acetate dihydrate and 0.035 mol boric acid" to "0.05 mol lithium nitrate, 0.05 mol aluminum nitrate nonahydrate, 0.02 mol zinc acetate dihydrate and 0.1 mol boric acid".
[0138] Performance testing:
[0139] The P of the soft magnetic composite material in this comparative example at 1MHz / 50mT was obtained by magnetic property testing. cv 2458mW / cm 3 The insulation and low-loss soft magnetic composite material of Example 2 (660mW / cm) is significantly higher. 3 The reason is that the formed glassy coating layer is too thick.
[0140] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A high-insulation, low-loss soft magnetic composite material, characterized in that, The composition includes soft magnetic powder with a low-melting-point glass insulating layer in situ coated on its surface; the low-melting-point glass insulating layer is composed of Li2O-Al2O3-ZnO-B2O3-SiO2 glass.
2. The high-insulation, low-loss soft magnetic composite material according to claim 1, characterized in that: The thickness of the low-melting-point glass insulating layer is 20nm to 100nm; and / or, the glass transition temperature of the Li2O-Al2O3-ZnO-B2O3-SiO2 glass is 450℃ to 520℃, and the softening point is ≤580℃.
3. The high-insulation, low-loss soft magnetic composite material according to claim 1 or 2, characterized in that: The soft magnetic powder is at least one of iron-silicon-aluminum powder, iron-nickel powder, iron-silicon powder, pure iron powder, and carbonyl iron powder; and / or, the D of the soft magnetic powder... 50 The particle size ranges from 5 μm to 100 μm.
4. A method for preparing a high-insulation, low-loss soft magnetic composite material as described in any one of claims 1 to 3, characterized in that, Includes the following steps: 1) Preparation of pretreated soft magnetic powder and composite sol precursor solution: Preparation of pretreated soft magnetic powder: The soft magnetic powder is acid-washed, water-washed and dried to obtain pretreated soft magnetic powder; Preparation of composite sol precursor: Lithium nitrate, aluminum nitrate, zinc acetate and boric acid are dissolved in water to prepare an aqueous solution, and tetraethyl orthosilicate is dissolved in ethanol to prepare an ethanol solution of tetraethyl orthosilicate. The aqueous solution is then slowly added to the ethanol solution of tetraethyl orthosilicate under stirring. After the addition is complete, the mixture is stirred to react and obtain the composite sol precursor. 2) Add the pretreated soft magnetic powder to the composite sol precursor solution, adjust the pH of the system to 8-10 and then react. Then separate, purify and dry the product to obtain the coated soft magnetic powder. 3) The coated soft magnetic powder is subjected to gradient heat treatment in an inert or reducing atmosphere: First stage: Control the heating rate to 2℃ / min~5℃ / min to raise the temperature from room temperature to 150℃~250℃, and hold for 0.5h~1h; Second stage: Control the heating rate at 1℃ / min~3℃ / min and continue heating to 480℃~580℃, and hold for 0.5h~2h; Third stage: Control the cooling rate to ≥10℃ / min to cool down to room temperature and obtain heat-treated soft magnetic powder; 4) Mix the heat-treated soft magnetic powder and lubricant, then mold it, and then anneal it in a protective atmosphere to obtain a high-insulation, low-loss soft magnetic composite material.
5. The preparation method according to claim 4, characterized in that: Step 1) The acid solution used for pickling is at least one of citric acid solution and dilute hydrochloric acid solution; and / or, the pickling method in step 1) is ultrasonic cleaning, and the pickling time is 10 min to 20 min.
6. The preparation method according to claim 4 or 5, characterized in that: In step 1), the molar ratio of tetraethyl orthosilicate, lithium nitrate, aluminum nitrate, zinc acetate, and boric acid is 1:0.05–0.40:0.05–0.25:0.05–0.20:0.1–1.0; and / or, the molar ratio of tetraethyl orthosilicate and water in step 1) is 1:4–25; and / or, the molar ratio of tetraethyl orthosilicate and ethanol in step 1) is 1:6–20; and / or, the stirring reaction time in step 1) is 30 min–60 min.
7. The preparation method according to claim 4, characterized in that: In step 2), the ratio of the pretreated soft magnetic powder to the composite sol precursor solution is 1g:6mL to 15mL; and / or, the reaction in step 2) is carried out at a temperature of 40℃ to 60℃ for a reaction time of 2h to 5h.
8. The preparation method according to claim 4, characterized in that: In step 4), the mass ratio of the soft magnetic powder to the lubricant is 1:0.003 to 0.015; and / or, in step 4), the lubricant is at least one of zinc stearate and lithium stearate.
9. The preparation method according to claim 4 or 8, characterized in that: Step 4) The compression molding is carried out under a pressure of 1000MPa to 1800MPa; and / or, Step 4) The annealing is carried out at a temperature of 650℃ to 700℃ for a time of 0.5h to 1h.
10. The application of a high-insulation, low-loss soft magnetic composite material as described in any one of claims 1 to 3 in new energy vehicle drive motors, 5G base station power supplies, or aerospace inductors.
